Pengaruh Pemasaran Media Sosial dan Mulut ke Mulut Secara Elektronik terhadap Loyalitas Pelanggan melalui Keterikatan Pelanggan Grab di Provinsi DKI Jakarta - Dirgantoro; Ismail Razak; Iwan Kurniawan Subagja (Jurnal Manajemen Bisnis Krisnadwipayana, 2026)
This study aims to analyze the influence of: 1) social media marketing and electronic word-of-mouth on customer engagement, 2) social media marketing and electronic word-of-mouth on customer loyalty, 3) customer engagement on customer loyalty, 4) social media marketing and electronic word-of-mouth influence customer loyalty through customer engagement. The study was conducted on Grab online transportation customers in Province DKI Jakarta as respondents. The sampling technique used insidental sampling. Data analysis methods used descriptive analysis and path analysis. The results show that: 1) social media marketing and electronic word-of-mouth have a positive and significant effect on customer engagement, 2) social media marketing and electronic word-of-mouth have a positive and significant effect on customer loyalty, 3) customer engagement has a positive and significant effect on customer loyalty, 4) social media marketing and electronic word-of-mouth have a positive and significant effect on customer loyalty through customer engagement.